Ice loss detection of glacierets in the Desert and Central Andes of Chile between 2018 and 2023 - Ugalde, Felipe; Valenzuela-Astudillo, Helena; Toledo, Martina; Carrasco, Javiera; Ruiz, Lucas; Apey, Ashley; Pinto, Diego; Marangunic, Cedomir (Frontiers in Earth Science, 2025)
Worldwide, the shrinkage of small glaciers has occurred more rapidly in recent decades, and the Desert and Central Andes of Chile are no exception. Among these ice bodies are glacierets, defined as glaciers with a reduced surface area of less than 25 km2. Their extensive and heterogeneous distribution along the Andes makes their analysis challenging, yet the limited number of studies documenting glacieret’s change presents an opportunity to deepen the understanding of their response to anthropogenic climate change. In this work, we seek to detect, at the end of the austral summer of 2023, the variation of visible ice surfaces of glacierets between the Arica y Parinacota Region and the Biobío Region. A combined remote sensing approach is applied to analyse their surface cover through the Normalised Difference Snow Index (NDSI) along with albedo and land surface temperature changes using satellite inputs from Landsat 8 and Sentinel-2 imagery. We validate our results through a visual inspection for all the small glacierets (area below 0.01 km2) using high-resolution optical imagery for the period 2018–2023. Lastly, we corroborate the observed trends with temperature and precipitation data from meteorological stations. Our results evidence a general reduction of the clean ice area of 16%, equivalent to a surface ice loss of −4.77 km2 for the 2019–2023 period for all 1,856 glacierets within the study area. This trend is shared by the smallest glacierets with more than 50% having no visible surface ice by 2023–2024, such that 77 glacierets are declared “entirely vanished” and 244 glacierets “presumably vanished,” with an ice loss of up to 1.49 km2. Additionally, we found that more than 34% of the glacierets analysed could be considered debris-covered, with most of them located below 5,000 m a.s.l. throughout the study area. The observed glacieret’s surface changes are supported by a precipitation reduction of up to 80% in mountainous areas when comparing the 2018–2023 period with previous decades (2000–2023). Our findings represent a valuable contribution to local and regional hydrological assessments, particularly for regions in the Desert and Central Andes of Chile already subjected to hydrological stress.